Généalogie générique du monologue dramatiquebrowningnien ; et du monopolylogue - Yann Tholoniat (Cahiers Victoriens et Edouardiens)
The dramatic monologue did not appear with Browning or Tennyson. But in order to reassess Robert Browning’s achievement, one might trace a line starting with Aristophanes’ dramatic use of the parabasis, evolving with the Roman satire, and going through John Donne’s game with the reader, conceived of as a silent auditor. Browning also put to good use the generic hybridity of his Romantic predecessors who endeavoured to master the spoken word within the written word. If Tennyson called Maud a monodrama, Browning’s most original generic achievement might be called a “monopolylogue”, that is to say a speech containing various voices uttered by only one speaker.